Hubungan Aktivitas Fisik dengan Tekanan Darah pada Perokok Dewasa - Rafitri, Desvia Cinta; Widodo, Gipta Galih; Sukarno; Puji Lestari (Indonesian Journal of Nursing Research (IJNR), 2025)
Blood pressure is an important indicator in assessing a person's cardiovascular health. Smoking can worsen blood pressure through the narrowing of blood vessels due to nicotine, while physical activity has the potential to lower blood pressure. However, the relationship between physical activity and blood pressure in adult smokers is still rarely studied. To determine the relationship between physical activity and blood pressure in adult smokers in Kesongo Village, Tuntang District, Semarang Regency. This study uses descriptive correlation. The population is 2,341 people, a sample of 96 respondents selected using purposive sampling with the criteria of active smokers aged 19-44 years. Physical activity was measured using the IPAQ (International Physical Activity Questionnaire) questionnaire and blood pressure using a digital sphygmomanometer. Most respondents had heavy physical activity (60.4%) and blood pressure in the pre-hypertension category (57.3% systolic, 24% diastolic). Statistical analysis with the Pearson product moment test showed a significant relationship between physical activity and systolic blood pressure with a weak positive relationship (r = 0.214, p = 0.036). Education on appropriate physical activity patterns for smokers is needed to optimize health benefits. Efforts to reduce smoking habits remain the main step in preventing hypertension. Abstrak Tekanan darah merupakan indikator penting dalam menilai Kesehatan kardiovaskular seseorang. Merokok dapat memperburuk tekanan darah melalui penyempitan pembuluh akibat nikotin, sementara aktivitas fisik berpotensi menurunkan tekanan darah. Namun, hubungan antara aktivitas fisik dan tekanan darah pada perokok dewasa masiah jarang diteliti. Mengetahui hubungan antara aktivitas fisik dengan tekanan darah pada perokok dewasa di Desa Kesongo, Kecamatan Tuntang, Kabupaten Semarang. Penelitian ini menggunakan deskriptif korelasional. Populasi 2.341 jiwa, sampel 96 responden yang dipilih menggunakan purposive sampling  dengan kriteria perokok aktif usia dewasa 19 – 44 tahun. Aktivitas fisik diukur dengan kuesioner IPAQ (International Physical Activity Questionnaire) dan tekanan darah menggunakan sphygmomanometer digital. Sebagian besar responden memiliki aktivitas fisik berat (60,4%) dan tekanan darah kategori pre-hipertensi (57,3% sistolik, 24% diastolik). Analisis stsatistik dengan uji pearson product moment menunjukkan terdapat hubungan signifikan antara aktiivtas fisik dan tekanan darah sistolik dengan hubungan positif yang lemah (r  = 0,214, p = 0,036). Diperlukan edukasi pola aktivitas fiisk yang sesuai bagi perokok untuk mengoptimalkan manfaat Kesehatan. Upaya pengurangan kebiasaan merokok tetap menajadi Langkah utama dalam pencegahan hipertensi.